2020
DOI: 10.1149/1945-7111/ab83e8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Water Splitting Performance of Ni/Si-doped TiO2 Photoanode Fabricated through Electrochemical Reduction in Aqueous Solutions

Abstract: Ni/Si-doped TiO2 nanostructures were prepared by anodizing Ti-1Ni-5Si alloy. The electrochemical reduction in the aqueous solutions was a simple and effective method to self-dope Ti3+ into Ni/Si-doped TiO2 nanostructures. It was found that electrochemical reduction in neutral aqueous solution (pH 7) was more effective than that in either acidic aqueous solution (pH 3) and basic aqueous solution (pH 13). The stable reduced Ni/Si-doped TiO2 photoanode obtained in the neutral aqueous solution exhibited an excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In addition, it was proved that electrochemical reduction could induce a type II structure, which enhances charge separation and transport 78 as well as creates self-doped Ti 3+ accompanied by increasing the amount of O vac in the TiO 2 photoanode. [79][80][81] These studies validate that electrochemical treatments not only can affect the surface/ interface properties of TiO 2 , but also improve its bulk attributes from time to time.…”
Section: Electrochemical Treatmentsmentioning
confidence: 72%
“…In addition, it was proved that electrochemical reduction could induce a type II structure, which enhances charge separation and transport 78 as well as creates self-doped Ti 3+ accompanied by increasing the amount of O vac in the TiO 2 photoanode. [79][80][81] These studies validate that electrochemical treatments not only can affect the surface/ interface properties of TiO 2 , but also improve its bulk attributes from time to time.…”
Section: Electrochemical Treatmentsmentioning
confidence: 72%
“…They found that Cr doping increases capacity and Na doping suppresses voltage-decay. Similar doping investigations using Mg, [24][25][26] Ni, [25][26][27][28][29][30][31][32][33][34][35] Co, 28,31,36,37 and N [38][39][40] on the electrode of lithium-ion batteries have demonstrated improved electrochemical performance.…”
mentioning
confidence: 80%
“…Such behavior was assigned to the many-body effects which are known causing shifting up of the valence band and shifting down of the conduction band resulting in the band gap shrinkage 8 . Narrowing the energy band gap upon Si doping was also assigned to the lattice shrinkage caused by the stronger electronegativity of Si (1.80) 32 over that of Cd (1.69).…”
Section: Optical Propertiesmentioning
confidence: 99%